2018
DOI: 10.1021/jacs.8b04063
|View full text |Cite
|
Sign up to set email alerts
|

Plug-and-Play Approach for Preparing Chromatin Containing Site-Specific DNA Modifications: The Influence of Chromatin Structure on Base Excision Repair

Abstract: The genomic DNA of eukaryotic cells exists in the form of chromatin, the structure of which controls the biochemical accessibility of the underlying DNA to effector proteins. In order to gain an in depth molecular understanding of how chromatin structure regulates DNA repair, detailed in vitro biochemical and biophysical studies are required. However, because of challenges associated with reconstituting nucleosome arrays containing site-specifically positioned DNA modifications, such studies have been limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 67 publications
(129 reference statements)
5
29
0
Order By: Relevance
“…S1) 19 . The minor sequence variations resulting from the inclusion of these restriction sites do not significantly alter the rotational positioning of the DNA relative to the native 601 sequence 19 . Treatment of 12-601-Nb with Nb.BbvCI resulted in formation of a short gap upon heat denaturation, which was subsequently filled in with a DNA oligonucleotide carrying the desired dU residue (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…S1) 19 . The minor sequence variations resulting from the inclusion of these restriction sites do not significantly alter the rotational positioning of the DNA relative to the native 601 sequence 19 . Treatment of 12-601-Nb with Nb.BbvCI resulted in formation of a short gap upon heat denaturation, which was subsequently filled in with a DNA oligonucleotide carrying the desired dU residue (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…We designed the 12 × 601 template ( 12-601-Nb ) to contain two proximal nicking endonuclease recognition sites (Nb.BbvCI) within the nucleosome-bound region of the fifth 601 repeat (N5), which enabled site-specific incorporation of single dU residue using our previously reported “plug-and-play” approach (see “Methods” section and Fig. S1) 19 . The minor sequence variations resulting from the inclusion of these restriction sites do not significantly alter the rotational positioning of the DNA relative to the native 601 sequence 19 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The biochemical activities of these glycosylases have been characterized in duplex DNA, however there have been fewer examinations of UDG and SMUG1 activity on chromatin or packaged DNA (36-40). The studies on packaged DNA have revealed that UDG and SMUG1 activity is generally lower than on duplex, and that local dynamics of the DNA and associated proteins can modulate activity.…”
Section: Introductionmentioning
confidence: 99%